2012
DOI: 10.1073/pnas.1115980109
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-3, an immune modulator in peripheral CD8 T-cell tolerance

Abstract: In healthy individuals, T cells react against incoming pathogens, but remain tolerant to self-antigens, thereby preventing autoimmune reactions. CD4 regulatory T cells are major contributors in induction and maintenance of peripheral tolerance, but a regulatory role has been also reported for several subsets of CD8 T cells. To determine the molecular basis of peripheral CD8 T-cell tolerance, we exploited a double transgenic mouse model in which CD8 T cells are neonatally tolerized following interaction with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 32 publications
(44 reference statements)
2
54
1
Order By: Relevance
“…We have recently demonstrated that DKK3 can act as a tissue-derived immune modulator that influences type and strength of local T cell responses in models of peripheral tolerance, transplantation, and autoimmune disease (27)(28)(29). We have found that DKK3 is expressed during kidney development, which occurs by a mesenchymal-epithelial transition.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…We have recently demonstrated that DKK3 can act as a tissue-derived immune modulator that influences type and strength of local T cell responses in models of peripheral tolerance, transplantation, and autoimmune disease (27)(28)(29). We have found that DKK3 is expressed during kidney development, which occurs by a mesenchymal-epithelial transition.…”
Section: Introductionmentioning
confidence: 91%
“…In order to assess whether direct blockade of DKK3 protein could corroborate the beneficial effect of the genetic DKK3 abrogation and to investigate the therapeutic potential of antibody-mediated DKK3 blockade, we treated WT UUO mice with either an anti-DKK3 monoclonal antibody or an isotype control. The specificity of the DKK3 antibody has been shown in experiments in which anti-DKK3 selectively targeted regulatory CD8 + T cells positive for DKK3 (28). The first antibody injection was done at surgery, followed by applications on every third day ( Figure 2A).…”
Section: Dkk3 Promotes Ta and Ifmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of mechanisms have been proposed to account for the inhibitory effects of Dkk-3 on tumor cell proliferation in cancer of the prostate and other organs (Abarzua et al, 2005;Kashiwakura et al, 2008;Lee et al, 2009;Lodygin et al, 2005;Yue et al, 2008). Despite the tumor suppressor activities of Dkk-3, homozygous deletion of the Dkk3 gene in mice has only minor effects on blood cell counts, lung ventilation and behaviour, with no reported increase in mortality or spontaneous tumor formation (del Barco Barrantes et al, 2006;Papatriantafyllou et al, 2012). A clue to the possible role of Dkk-3 in normal tissues comes from siRNA studies in prostate epithelial cells, where Dkk-3 expression is required for formation of acini in three-dimensional (3D) Matrigel cultures (Kawano et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is also present in the blood (27). We have shown previously that DKK3 could limit CD8 T cell reactivity (28). Therefore, we were interested in whether DKK3 could also affect B cell function.…”
mentioning
confidence: 99%